Failure Assessment Diagram Constraint Used for Integrity Analysis of Cylindrical Shell with Crack - Akbar, Musthafa; Setiawan, Rachman (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
During itsoperation time, cylindrical pressure vessel could experience cracks. If this happens, the question is raised whether the pressure vessel could still be used or not, moreoever whether further treatment is required. In process and petroleum industry, an integrity analysis using Fitness For Service methodology is common, for instance referring to API 579/ASME FFS-1 2007 Code. Level 3 assessment within the Code requires a finite element simulation in order to generate both the evaluation point and the Failure Assessment Diagram (FAD) that serves as an acceptance criteria. Here, a parametric study based on the methodology given by the Code has been carried out to generate such result for the cases of internal longitudinal crack defect in a cylindrical shells for a number of common cases, in terms of thickness-to-radius ratio, crack size ratio, and crack aspect ratio. The evaluation of Stress Intensity Factor is determined through J-integral parameter found using a finite element analysis with a specially-meshed strategy incorporating the crack. The result of the model is first verified with that of the Code for a number of cases, before being used for parametric study. The model yields a relatively close comparison with that of the Code. A number of regressed equation was derived for several cases, and proposed to be used in integrity assessment of cylindrical shell. A procedure of using the parametric study result from this investigation is also outlined here.